Health Behaviors and Risk Factors Among American Indians and Alaska Natives, 2000–2010 - Cobb, Nathaniel (American Public Health Association, 2014)
Objectives. We provided contextual risk factor information for a special supplement on causes of death among American Indians and Alaska Natives (AI/ANs). We analyzed 11 years of Behavioral Risk Factor Surveillance System (BRFSS) data for AI/AN respondents in the United States. Methods. We combined BRFSS data from 2000 to 2010 to determine the prevalence of selected risk factors for AI/AN and White respondents residing in Indian Health Service Contract Health Service Delivery Area counties. Regional prevalence estimates for AI/AN respondents were compared with the estimates for White respondents for all regions combined; respondents of Hispanic origin were excluded. Results. With some regional exceptions, AI/AN people had high prevalence estimates of tobacco use, obesity, and physical inactivity, and low prevalence estimates of fruit and vegetable consumption, cancer screening, and seatbelt use. Conclusions. These behavioral risk factors were consistent with observed patterns of mortality and chronic disease among AI/AN persons. All are amenable to public health intervention.